Revised Diffusion Law Permits Quantitative Nanoscale Characterization of Membrane Organization - Svobodová, Barbora; Št'astný, David; Blom, Hans; Mikhalyov, Ilya; Gretskaya, Natalia; Balleková, Alena; Sezgin, Erdinc; Hof, Martin; Šachl, Radek (Analytical chemistry, 2025)
The formation of functional nanoscopic domains is an inherent property of plasma membranes. Stimulated emission depletion combined with fluorescence correlation spectroscopy (STED-FCS) has been previously used to identify such domains; however, the information obtained by STED-FCS has been limited to the presence of such domains while crucial parameters have not been accessible, such as size (Rd), the fraction of occupied membrane surface (f), in-membrane lipid diffusion inside (Din) and outside (Dout) the nanodomains as well as their self-diffusion (Dd). Here, we introduce a quantitative approach based on a revised interpretation of the diffusion law. By analyzing experimentally recorded STED-FCS diffusion law plots using a comprehensive library of simulated diffusion law plots, we extract these five parameters from STED-FCS data. That approach is verified on ganglioside nanodomains in giant unilamellar vesicles, validating the Saffman-Delbrück assumption for Dd. STED-FCS data in both plasma membranes of living PtK2 cells and giant plasma membrane vesicles are examined, and a quantitative framework for molecular diffusion modes in biological membranes is presented.
Keywords: Unilamellar Liposomes; Cell Membrane; Diffusion; Spectrometry, Fluorescence; difuze; Animals; unilamelární lipozómy; fluorescenční spektrometrie; zvířata; buněčná membrána